PENGARUH RASIO PROFITABILITAS DAN LEVERAGE TERHADAP PERTUMBUHAN LABA PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE JANUARI SAMPAI SEPTEMBER TAHUN 2023 - Ni Made Putri Nanda Prasetya; Ni Wayan Suartini; Komang Asri Pratiwi (Nusantara Hasana Journal, 2024)
This study aims to determine the effect of the ratio profitability and leverage ratios on the profit growth of sectors listed on the Indonesia Stock Exchange (IDX) from January to September 2023. This research is organized descriptively using a quantitative approach method. The population in this study is a Banking Company that has been listed on the Indonesia Stock Exchange (IDX).on the Indonesia Stock Exchange (IDX). The research sample in this company is Financial Statements of banking companies that have been listed on the Indonesia Stock Exchange which are obtained from the IDX for the period January to September 2023. Technique sampling technique using purposive sampling method, which is a non-probability sampling method. non-probability sampling method. Data collection can be done by various data sources, namely, secondary data. The results of this study are Variable Ratio profitability ratio variable (X1) has a positive effect on profit growth (Y) can be seen from the significance value of 0.018 <0.05 and the seen from the significance value of 0.018 <0.05 and the value of t-count value of 2.409> 1.983. Leverage variable (X2) has a negative effect on earnings growth (Y). profit (Y). This can be seen from the obtained significance value of 0.237> 0.05 and the t-count value of -1.190 < 1.983. While the variable profitability ratio (X1) and leverage (X2) have a significant effect on stock growth (Y). stock (Y). This can be seen from the significance value of 0.001<0.05 and the F-count value of 6.428> 2.96 with a coefficient value of 0.001 <0.05. which shows a positive direction, so that the Profitability and Leverage Ratioshave a significant effect on Profit Growth in the Banking Sector.